2020
DOI: 10.1016/j.nicl.2020.102453
|View full text |Cite
|
Sign up to set email alerts
|

Parieto-occipital sulcus widening differentiates posterior cortical atrophy from typical Alzheimer disease

Abstract: Highlights Parieto-occipital sulcus visual rating scale can distinguish PCA from typical AD. Visual rating scales have been validated using VBM and Brainvisa Morphologist. Visual rating score reflects sulcal widening rather than grey matter reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Recent investigations have revealed insights into the genetic architecture of sulcal depth 15 but genetic factors influencing other important and heritable features, such as sulcal width, depth and surface area, have not been examined at comparable scale 16 , 17 . Measures of sulcal morphology can serve as sensitive markers of aging 21 , 22 , 36 and intelligence 37 , and effects on these measures are partially independent of those on cortical thickness or surface area 38 . Thus, studying genetic influences on brain sulci may complement investigations of more traditional structural measures, offering greater understanding of the mechanisms guiding variation in human brain organisation and downstream associations with human health and disease 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations have revealed insights into the genetic architecture of sulcal depth 15 but genetic factors influencing other important and heritable features, such as sulcal width, depth and surface area, have not been examined at comparable scale 16 , 17 . Measures of sulcal morphology can serve as sensitive markers of aging 21 , 22 , 36 and intelligence 37 , and effects on these measures are partially independent of those on cortical thickness or surface area 38 . Thus, studying genetic influences on brain sulci may complement investigations of more traditional structural measures, offering greater understanding of the mechanisms guiding variation in human brain organisation and downstream associations with human health and disease 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Both measurements have a sensitivity of over 75% and a specificity of over 80%; Similarly, in the PA and GCA-F visual rating scales, some studies have demonstrated a good correlation between the PA visual rating scale with the automated tool. In the meantime, the different severity scores in the rating scale corresponded to different quantitative degrees of atrophy ( 44 , 45 ). When comparing frontal lobe atrophy, Ferreira et al ( 33 ) measured used fully automated and manual tracings quantitative imaging methods and provided a comprehensive validation with the GCA-F visual rating scale.…”
Section: Discussionmentioning
confidence: 99%
“…The sample of 15 HCs (7 females, 46.7%) had comparable mean age (69.5±6.52) and education (7.78). Their mean MMSE score was 29.25±0.96 [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…We used as reference data the atrophy scores obtained by the same visual scales from a small sample of 15 healthy controls recruited in the Neurologic Unit of the same Hospital. This sample has been described in a previous article [ 32 ]. Considering the functional imaging, we resumed the [ 18 F]-FDG PET scan outcomes and made a comparison between CM-AD and CA-AD patients on them, by considering medial temporal hypo-metabolism, cortical regions targeted, and asymmetries in glucose metabolism reduction.…”
Section: Methodsmentioning
confidence: 99%